Search for the decay B0s→D[bar]0[function]0(980) - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; et al. (Journal of high energy physics, 2015)
A search for Bs0→D¯0f0980 decays is performed using 3.0 fb1− of pp collision data recorded by the LHCb experiment during 2011 and 2012. The f0(980) meson is reconstructed through its decay to the π+π− final state in the mass window 900 MeV/c2 < m(π+π−) < 1080 MeV/c2. No significant signal is observed. The first upper limits on the branching fraction of ℬBs0→D¯0f0980<3.13.4×10−6 are set at 90 % (95 %) confidence level.
Im Titel sind "0" und "s" untereinander geschrieben: "0" hochgestellt, "s" tiefgestellt
Im Titel steht "D" mit Oberstrich und hochgestellter "0"
Im Titel ist "function" als mathematisches Zeichen dargestellt, die Zahl "0" dabei tiefgestellt
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, P. d'Argent, B. Adeva, M. Adinolfi, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, K. Matthieu, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 667 weitere]
Gesehen am 24.11.2020